What’s Left for the WTO? - Bown, Chad P. (World Bank, Washington, DC, 2015)
Suppose that when addressing the question of “what’s left for the WTO?,” tariff negotiators relied not on the agenda established in 2001 but instead on the terms-of-trade theory of trade agreements to identify negotiating priorities. This paper uses the lens of the terms-of-trade theory to investigate three areas in which it is frequently alleged that currently applied tariffs remain “too high”; the implication being that the WTO’s job performance to date is incomplete. This includes applied tariffs for countries that are not members of the WTO, applied MFN tariffs for WTO members that are unbound, and applied MFN tariffs for WTO members set in the presence of large amounts of tariff binding overhang. These are almost exclusively the domain of developing countries’ own trade policies and they are collectively important; 3.5 billion people currently live in countries in which the WTO has had minimal effect for one of these three reasons. This paper builds upon recent developments in the empirical literature to present evidence—some direct, some indirect—that sheds light on each area. It then identifies specific needs for additional research to clarify policy implications for the future role of the WTO in the ever-changing international trading system.